PEDAGOGICAL FEATURES OF PRACTICAL PHYSICAL TRAINING OF STUDENTS OF THE ACADEMIC LYCEUM OF THE MINISTRY OF INTERNAL AFFAIRS OF THE REPUBLIC OF UZBEKISTAN (American Journal of Pedagogical and Educational Research, 2023)
This article describes in detail the practical physical training of academic high school students.